Evaluasi Proses Pelayanan Administrasi Kependudukan dengan Metode Lean Office - Henra Nanang Sukma; Elita Amrina; Alizar Hasan (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
The problems occurred at the Pelalawan Population and Civil Registration Service are wasteful in the time of service for population administration. Therefore, this study aims to make improvements in reducing waste of service time and provide recommendations for managing the administrative service process, thus, it can be used as a reference in the process of improving government service organizations. The method used is the Define, Measure, Analyze, Improve, and Control (DMAIC) method, by removing unproductive process steps, which focus on measurements, and applying technology to improve the quality of the target towards Six-Sigma. The results obtained by following the DMAIC process are the smallest timeliness in providing services with a gap value=(-1,196), σ=1,62; the ease of the service procedure with the gap value=(-0,917), σ=1,76; the competence of the officers in the service with the gap value=(-0,897), σ=1,76; and written and electronic information resources that are needed by the gap value=(-0,876), σ=1,78. The study proposes improvements by creating digital document archive settings, conducting the performance measurements using VSM map, building the queue system, creating a flow of services, designing a one door services, and improving the quality of resources by training the officers.